2022
DOI: 10.3390/jcm11082266
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Osteomyelitis and Infective Endocarditis Co-Infection

Abstract: Many cases of vertebral osteomyelitis (VO) and infective endocarditis (IE) co-infection have been reported, and it has been recognized that attention should be paid to the possibility of both diseases co-existing during diagnosis and treatment. However, the incidence, clinical status, and outcomes of IE in patients with VO remain unclear. For this study, the eligibility criteria for patient recruitment included all cases of VO at the five medical university hospitals. Patients with a history of spinal surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Nevertheless, in the present case, the multiple adjustments of the pacemaker on the same side cannot preclude the device infection from existing skin flora. It has been reported that a six-week antimicrobial treatment of spondylodiscitisassociated IE has been efficient without the increased risk of relapse [17][18][19]. Hence, the present patient was treated with an appropriate antimicrobial combination for 40 days, followed by the installation of a new pacemaker on the contralateral side, Regarding CDRIE, most studies recommend device and lead replacement for radical treatment as in the present case [20].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, in the present case, the multiple adjustments of the pacemaker on the same side cannot preclude the device infection from existing skin flora. It has been reported that a six-week antimicrobial treatment of spondylodiscitisassociated IE has been efficient without the increased risk of relapse [17][18][19]. Hence, the present patient was treated with an appropriate antimicrobial combination for 40 days, followed by the installation of a new pacemaker on the contralateral side, Regarding CDRIE, most studies recommend device and lead replacement for radical treatment as in the present case [20].…”
Section: Discussionmentioning
confidence: 71%
“…The pathogenesis connecting the two infections remains unclear and a matter of debate. However, irrespective of the exact pathogenesis, the association of spondylodiscitis and IE should always be considered, especially in cases with suspicious relevant symptoms [15,[17][18][19]. Nevertheless, in the present case, the multiple adjustments of the pacemaker on the same side cannot preclude the device infection from existing skin flora.…”
Section: Discussionmentioning
confidence: 79%
“…Several recent studies detected infective endocarditis (IE) in 10–15 % of patients with vertebral osteomyelitis. [13] , [14] Other studies have reported coinfection rates as high as 33 % with variation due to patient demographics (higher rates of IE were reported in older and male patients) and sensitivity of imaging modalities. [15] Infective endocarditis (IE) should be considered in all cases of vertebral osteomyelitis especially in elderly patients and those with a history of valvulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The lumbar spine is the most prevalent site of pyogenic infection involvement, followed by the thoracic, cervical, and sacral regions [5] . Vertebral osteomyelitis is frequently linked to infections in distant sites, including urinary tract infections, infective endocarditis (IE), intestinal infections, and skin infections through the hematogenous pathway [6] . The rise in the occurrence of hematogenous vertebral osteomyelitis (HVO) among young patients is connected to the expanding population of intravenous drug users and endocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, clinicians, particularly spine surgeons and internal medicine physicians dealing with VO cases, must maintain a heightened awareness of IE to prevent overlooking this significant complication. Regular echocardiograms and multiple sets of blood cultures should be routinely conducted to ensure timely diagnosis and implement supportive therapy, which is crucial for minimizing morbidity and mortality [6] . Also, in individuals suspected of hematogenous vertebral osteomyelitis and having an intravascular catheter or device, it is advisable to collect blood cultures.…”
Section: Introductionmentioning
confidence: 99%